The role of green start-ups in the transition to a circular economy: International experiences - Aymene, Boudendouna Mohammed; Mounir, Louadj (International journal of economic perspectives, 2024)
Amidst escalating environmental crises, such as global warming, numerous organizations have initiated quests for viable solutions to these distressing phenomena. The escalating global temperatures and the consequential issues have catalysed opportunities for innovators and pioneers to contribute towards sustainable development, encompassing its three critical dimensions: social, environmental, and economic. This impetus has given rise to sustainable enterprises or green start-ups, though these firms are predominantly still in their embryonic stages, particularly in Arab nations, and notably in Algeria. The nascent state of these companies can be attributed to inadequate funding, primarily due to investors’ hesitancy to allocate resources towards them and the legal ambiguities that currently envelop these green startups.